Lactobacillus rhamnosus-derived extracellular vesicles influence calcium deposition in a model of breast cancer intraductal calcium stress - Ngoc Vuong; Melany Alomia; Ahana Byne; Purva Gade; Thomas Raymond Philipson; Rayan Ibrahim Alhammad; Cade J. Skislak; Intisar Alruwaili; Fahad M. Alsaab; Weidong Zhou; Marissa Howard; Andrea Brothers; et al. (iScience)
Summary: Extracellular calcium export by the breast ductal epithelium is crucial during lactation and plays a significant role in breast cancer progression. Intraductal calcium deposition is a hallmark of aggressive premalignant lesions. This study tested the hypothesis that microbiome-derived extracellular vesicles (EVs) influence calcium modulation in premalignant breast cancer lesions. Based on the analysis of plasma, serum, saliva, and tissue collected from breast cancer patients and controls (N = 150), Lactobacillus rhamnosus (Lr) was chosen as the model microbiota. In a BT-474 human breast cancer cell line monolayer culture under acute calcium stress, Lr EVs enhanced intracellular calcium intake. In a BT474 3D spheroid model under chronic calcium stress, Lr EVs increased extracellular calcium deposition and mRNA expression of calcium export channel plasma membrane calcium-transporting ATPase 2 (PMCA2) and stromal interaction molecule 1 (STIM1) in a dose-dependent manner. We propose that Lr EVs influence calcium regulation and mineral deposition, thereby affecting premalignant breast cancer progression.